Oral delivery strategies for nutraceuticals: Delivery vehicles and absorption enhancers. (July 2016) - Gleeson, John P.; Ryan, Sinéad M.; Brayden, David J.
Abstract: Background: Lifestyle issues contribute to the development of obesity, type 2 diabetes, and cardiovascular disease. Together with appropriate diet and exercise, nutraceuticals may contribute to managing prevention at an early stage prior to therapeutic intervention. However, many useful food-derived bioactive compounds will not sufficiently permeate the small intestine to yield efficacy without appropriate oral delivery technology. The pharmaceutical industry uses commercialised approaches for oral delivery including solubilizing technologies for small molecules, which could be applied to selected nutraceuticals with solubility issues. Systems currently being studied for labile and poorly permeable hydrophilic peptides and macromolecules include nanoparticles, intestinal permeation enhancers (PE) and mucolytics. These may also have potential for application to nutraceuticals with similar sub-optimal physicochemical characteristics. Scope and approach: We introduce factors which effect oral delivery of four types of nutraceuticals, namely fatty acids, bioactive peptides, micronutrients, and phytochemicals. Factors preventing oral absorption can arise from molecule physicochemical characteristics, which influence solubility, stability, and epithelial permeability in the gastrointestinal tract (GIT). We highlight the potential of selected delivery strategies to improve oral bioavailability of different types of nutraceuticals. Key findings and conclusions: There is an opportunity for the nutraceutical industry to leverage the pharmaceutical industry's progress in oral drug delivery. The use of delivery approaches using formulation with excipients or substances with a history of use in man has potential to improve solubility, stability, or permeability of nutraceuticals, leading to improved oral bioavailability. Leveraging oral delivery formulation approaches across nutraceutical and pharmaceutical molecules will lead to synergies for both fields. Highlights: Nutraceuticals have potential for health benefits if presented in appropriate oral delivery formats. Food-derived bioactive compounds are hampered by physicochemical and physiological barriers which limit oral bioavailability. Adapting oral delivery approaches using excipients from the pharmaceutical industry to nutraceuticals can enhance delivery. Nanoparticle systems may also improve solubility and permeability of nutraceuticals.